Rapid Determination of Bi (III) and Al (III) in Pharmaceutical Formulations using Organic Reagent Spectrophotometrically - Jumana W. Ammar (Journal of Global Pharma Technology, 2020)
A new trend describes the development and validation of a simple, sensitive and selective spectrophotometric methods for the determination of Bi (III) and Al (III) in pharmaceutical formulations have been conducted. In this paper, 4-(4 acetamidophenylazo) pyrogallol was synthesized as a new organic compound, 4-APAP, by coupling pyrogallol with diazotized p- aminoacetanilide in medium of controlled pH. 4- APAP was characterized by techniques of FT-IR, H-NMR, GC-Mass, TG and DSC thermal analysis methods. Solvatochromic behavior in solvents of various polarities was also investigated.Keywords: Pharmaceutical applications, Pyrogallol, Bi (III), Al (III).